2008
DOI: 10.1677/jme-08-0077
|View full text |Cite
|
Sign up to set email alerts
|

The role of JUN in the regulation of PRKCC-mediated STAR expression and steroidogenesis in mouse Leydig cells

Abstract: Activator protein 1

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(37 citation statements)
references
References 59 publications
1
36
0
Order By: Relevance
“…Anti-STAT3 shRNA (5Ј-CCAATTGTGATGCCTCCTT-3Ј), 26 anti-BAK1 shRNA (5Ј-TGCCTACGAACTCTTCACCTT-3Ј), 27 anti-JUN shRNAs (5Ј-GATGGAAACGACCTTCTA-3Ј and 5Ј-CAGTAACCCTAA-GATCCTA-3Ј referred to as shRNA#1 and shRNA#2, respectively) 28,29 lentiviral transgene plasmids pdcH1-shRNA-SR and pdcH1-Gl4-SR (shRNA-control) were cloned as previously described. 30 All shRNAlentiviral constructs encode RFP (red fluorescent protein) as a reporter gene.…”
Section: Dna Constructs Oligonucleotides and Site-directed Mutagenesismentioning
confidence: 99%
See 1 more Smart Citation
“…Anti-STAT3 shRNA (5Ј-CCAATTGTGATGCCTCCTT-3Ј), 26 anti-BAK1 shRNA (5Ј-TGCCTACGAACTCTTCACCTT-3Ј), 27 anti-JUN shRNAs (5Ј-GATGGAAACGACCTTCTA-3Ј and 5Ј-CAGTAACCCTAA-GATCCTA-3Ј referred to as shRNA#1 and shRNA#2, respectively) 28,29 lentiviral transgene plasmids pdcH1-shRNA-SR and pdcH1-Gl4-SR (shRNA-control) were cloned as previously described. 30 All shRNAlentiviral constructs encode RFP (red fluorescent protein) as a reporter gene.…”
Section: Dna Constructs Oligonucleotides and Site-directed Mutagenesismentioning
confidence: 99%
“…RNA22 allows identification of miRNA/mRNA binding even in the presence of nucleotide mismatches within the seed sequence. For gene-specific RNAi, we lentivirally expressed published shRNAs 28,29 predicted to target both c-JUN and JUND (shRNA#1) or c-JUN only (shRNA#2; Figure 7A). As shown in Figure 7B, miR-125b reduced expression of both c-JUN and JUND by approximately 50% and 60%, respectively.…”
Section: Mir-125b Regulates Expression Of C-jun and Jundmentioning
confidence: 99%
“…Transfection with PKC␣, -␦, and -and PKD small interfering RNAs (siRNAs) was performed using X-tremeGENE siRNA transfection reagent (Roche), using the procedures described previously (38,41). Silencer negative control, and the PKC␣ (no.…”
Section: Cells Plasmids Transfections and Luciferase Assaysmentioning
confidence: 99%
“…Immunoblotting studies were carried out using total cellular protein (25,26,41). Equal amounts of total protein (20 -30 g) were solubilized in sample buffer and loaded onto either 8 or 10% SDS-PAGE (Mini Protean II System; Bio-Rad Laboratories, Inc., Hercules, CA).…”
Section: Immunoblottingmentioning
confidence: 99%
“…Recently, several groups have reported that the ERK1/2, JNK and p38 MAP kinases are involved in the regulation of testosterone production [15][16][17] in response to a variety of extracellular factors, including LH, 18 interleukin-1a 15 and human chorionic gonadotropin.…”
Section: Introductionmentioning
confidence: 99%